The Efficacy of Daptomycin versus Vancomycin for MRSA Bloodstream Infection in Patients with Impaired Renal Function. - Weston, Adam. (2017)
Abstract: Background: There is an increasing use of daptomycin for Methicillin-resistant Staphylococcus Aureus (MRSA) bloodstream infections. However, there has been concern regarding its efficacy in patients with impaired renal function, reflected in a recent package insert change by the FDA. However, this decision was based on a small, post-hoc subgroup analysis and it is unclear whether this is a true association. Methods: We performed a single center, retrospective cohort study of patients with MRSA bloodstream infection who received at least 3 consecutive days of either vancomycin or daptomycin. Vancomycin treated patients were matched 2:1 with daptomycin patients using a propensity score built to estimate their propensity to receive daptomycin, n=150 total. After matching, additional conditional logistic regression was used to evaluate for outcome of treatment failure (a composite of in hospital mortality, persistent bacteremia, or recurrence) in vancomycin vs. daptomycin treated subjects across various renal functions. Results: In our multivariable model, neither the usage of daptomycin (OR 0.45, 95% CI 0.11-1.79) nor a GFR of <50 ml/min/1.73m2 (OR 1.06, 95%CI 0.4-2.86) were significantly associated with treatment failure (Table 3). Additionally, there was no significant interaction between them (p=0.6) indicating that the effect of daptomycin, compared to vancomycin, did not differ significantly in patients with either a GFR greater than or less than 50 ml/min/1.73m2. Similar non-significant results were seen for the individual outcomes of mortality, persistent bacteremia, and recurrence. In addition, there was no significant variation of the treatment effect of the use of daptomycin across the stages of chronic kidney disease. Conclusions: In our study we did not find a significant interaction of renal function with antibiotic choice. However, our sample size was small and smaller effects may be significant in a larger prospective trial.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: David Snydman.; Committee: Yoav Golan, Christina Holcroft, and John Griffith.; Keyword: Health sciences.